2017
DOI: 10.1186/s12877-017-0437-0
|View full text |Cite
|
Sign up to set email alerts
|

Expenditures of medicine use in hypertensive/diabetic elderly and physical activity and engagement in walking: cross secctional analysis of SABE Survey

Abstract: BackgroundThe literature shows the inverse association between physical activity level (PAL) and chronic diseases that have a significant burden over health care costs. However, in upper-middle income countries and in elderly population this information are scarce.ObjectiveTo describe the annual drug expenditures for the hypertensive and diabetic elderly population in Brazil and to analyze the association with PAL and engagement in walking.MethodsThis cross sectional study is part of SABE Survey and comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Six studies reported the number of days participants adhered to exercise in the last 7 days and most studies ( N = 4) found participants engaging in physical/exercise for less than 3 days in a week. Adherence rates ranged from 26.7% of older persons with diabetes from Brazil reportedly being sufficiently active (Bueno et al, ) to 69.0% of a sample of Nigerian type 2 diabetes individuals being physically active (Oyewole, Odusan, Oritogun, & Idowu, ). The median adherence among these studies was 41.2% (IQR = 29.5–50.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the number of days participants adhered to exercise in the last 7 days and most studies ( N = 4) found participants engaging in physical/exercise for less than 3 days in a week. Adherence rates ranged from 26.7% of older persons with diabetes from Brazil reportedly being sufficiently active (Bueno et al, ) to 69.0% of a sample of Nigerian type 2 diabetes individuals being physically active (Oyewole, Odusan, Oritogun, & Idowu, ). The median adherence among these studies was 41.2% (IQR = 29.5–50.1%).…”
Section: Resultsmentioning
confidence: 99%
“…All the procedures of the sampling process (elderly and domicile-based), data collection, and elaboration of the database have been previously published 17,18 . The questionnaire used for the study was that proposed by PAHO, translated and adapted for use in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information about the sampling procedures and data collection process have been described elsewhere 15,16 .…”
Section: Study Populationmentioning
confidence: 99%